Risk for social anxiety in early adolescence: Longitudinal impact of pubertal development, appearance comparisons, and peer connections. (July 2022) - Rapee, Ronald M.; Magson, Natasha R.; Forbes, Miriam K.; Richardson, Cele E.; Johnco, Carly J.; Oar, Ella L.; Fardouly, Jasmine
Abstract: Objectives: The aims of this study were to determine the impact of adolescent-relevant risk factors on changes in social anxiety symptoms from pre-to early-adolescence. Methods: From 2016 to 2018, 528 youth (51% boys) were tested in three annual waves across grades 6, 7, and 8 (M ages 11.2, 12.7, 13.7 years). Through online surveys youth reported on peer relationships that were combined into two latent factors: 1) appearance comparisons, comprising youth reports of appearance comparisons relative to others in general and while using social media, along with perceived attractiveness; and 2) positive peer connections, comprising youth reports of group affiliation, school belonging, and peer victimisation. Youth and their parents also reported on the youth's level of pubertal development as well as the youth's level of social anxiety using previously validated questionnaires. Social anxiety was also assessed with structured diagnostic interview. Results: Separate cross-lagged panel models were used to model longitudinal associations between all risk factors and youth, parent, and interviewer-reported measures of social anxiety. Of the associations tested, only appearance comparisons directly predicted increases in social anxiety symptoms 12 months later across all models. More advanced pubertal development was associated with increased appearance comparisons the following year. On the other hand, higher levels of social anxiety predicted subsequent reductions in positive peer connections in parent and interviewer models. Conclusions: These results highlight the important and interconnected impact of pubertal development and appearance comparisons on both the development of social anxiety symptoms during early adolescence, as well as the social consequences of social anxiety. Highlights: Social anxiety disorder commonly begins during early adolescence. Comparing one's appearance against others predicted social anxiety the following year. More advanced pubertal development indirectly predicted social anxiety. Poor peer connections did not predict future social anxiety. However, higher levels of social anxiety predicted poorer peer connections.